Answer:
40 N
Explanation:
The gravitational force between the asteroid and the spaceship is given by:
[tex]F=G\frac{mM}{R^2}[/tex]
where
[tex]G=6.67\cdot 10^{-11} m^3 kg^{-1} s^{-2}[/tex] is the gravitational constant
[tex]M[/tex] is the mass of the asteroid
[tex]m[/tex] is the mass of the spaceship
[tex]R[/tex] is the distance between the asteroid and the spaceship
The initial force is equal to:
[tex]F=G\frac{mM}{R^2}=360 N[/tex]
Later, the spaceship moves to a position 3 times as far from the center of the asteroid, so R' = 3R. Therefore, the new force will be
[tex]F'=G\frac{mM}{R'^2}=G\frac{mM}{(3R)^2}=G\frac{mM}{9R^2}=\frac{1}{9}F[/tex]
so, the force is decreased by a factor 9. Since the initial force was F=360 N, the new force will be
[tex]F'=\frac{360 N}{9}=40 N[/tex]